Field evaluation of sunflower (Helianthus annuus L.) accessions for resistance against leaf hopper, Amrasca biguttula biguttula (Ishida) - Selvanarayanan, Amala Hyacinth, A.M.* and V. (Journal of Phytology, 2011)
One hundred and twelve accessions of sunflower (Helianthus annuus L.) were screened under field conditions in two seasons at Sambavar Vadakarai and Udappankulam villages of Tirunelveli district of Tamilnadu, India during January to April and June to September, 2009 respectively for their resistance against leaf hopper (Amrasca biguttula biguttula Ishida). Observations on the number of nymphs/adults per plant were recorded at weekly interval. In the first season, four accessions viz., KBSH 1, AHT 14, GK 2002 and GMU 698 harboured the least population whereas in the second season, the accession KBSH 1 proved to be promising.